2002
DOI: 10.1051/0004-6361:20021287
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of comet C/1999 S4 LINEAR

Abstract: Abstract. Current models of the formation of comets in the Solar System assume that the most likely formation site for these pristine objects is in the Uranus-Neptune zone or just beyond with subsequent dynamical ejection by the growing protoplanets to distant orbits to form the Oort cloud. However, the composition of the recently disintegrated comet C/1999 S4 LINEAR suggests that it was most likely formed in the Jupiter-Saturn region (Mumma et al. 2001b;Kawakita et al. 2001). In this paper we argue that comet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
14

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 42 publications
1
16
0
14
Order By: Relevance
“…Cantat- Gaudin et al (2018a) were unable to identify any such co-moving group in the Gaia DR2 catalogue, and Kos et al (2018) also failed to identify one despite complementing the Gaia DR2 data with new high-resolution spectroscopy. They also point out that not a single pair of stars in the entire member lists of Bouchet & The (1983), Pavani et al (2001), de la Fuente Marcos et al (2013), and Kharchenko et al (2013) have matching astrometric parameters. NGC 1252 is listed as an asterism in Bica et al (2019) and Angelo et al (2019b).…”
Section: Appendix A: Notes On Individual Asterismsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cantat- Gaudin et al (2018a) were unable to identify any such co-moving group in the Gaia DR2 catalogue, and Kos et al (2018) also failed to identify one despite complementing the Gaia DR2 data with new high-resolution spectroscopy. They also point out that not a single pair of stars in the entire member lists of Bouchet & The (1983), Pavani et al (2001), de la Fuente Marcos et al (2013), and Kharchenko et al (2013) have matching astrometric parameters. NGC 1252 is listed as an asterism in Bica et al (2019) and Angelo et al (2019b).…”
Section: Appendix A: Notes On Individual Asterismsmentioning
confidence: 98%
“…The object is included in the DAML and MWSC catalogues (with quoted distances of 790 and 944 pc, respectively) and is also present in the study of Pavani & Bica (2007). de la Fuente Marcos et al (2013) collected additional data and reported that most stars in the investigated region are 'chemically, kinematically, and spatially unrelated to each other' but still argue that a handful of faint stars might be co-moving, making this 'enigmatic object' the first old, high-altitude (b = −50.8 • ), nearby open cluster. Kharchenko et al (2013) also provide the result of an isochrone fitting procedure for NGC 1252, indicating an old age of log t=9.5…”
Section: Appendix A: Notes On Individual Asterismsmentioning
confidence: 99%
“…For instance, the functionalization of peptides with gold nanoparticles to afford biocompatible nanoparticles able to penetrate the cell membrane and target the nucleus has been described recently. [31][32][33] In addition, a number of gold conjugates derived from amino acids or peptides have been reported. As examples, N-heterocyclic carbene (NHC)-gold complexes, [34,35] conjugates of ferrocene coordinated to gold(I) derivatives, [36] gold(III) dithiocarbamates, [37,38] gold(I) azides, [39] and gold(I) thi-of the phosphorus atom to the gold(I) centre, as evidenced by the downfield displacement of the singlets in the 31 P{ 1 H} NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…It may be argued that both peaks in the distribution of radial velocity in Fig. 1, bottom panel, could be the result of the presence of small, distant, and decaying clusters such as E 3 (de la Fuente Marcos et al 2015). In such cases, we should observe very small concentrations of relevant sources.…”
Section: Discussionmentioning
confidence: 89%